To each their own: sociodemographic disparities in student mental health - De Groot, Kristel; Wieman, Sander M.; Van Strien, Jan W.; Lindemann, Oliver (Frontiers in Education, 2024)
Research has demonstrated high rates of mental health problems in university students, and even higher rates in students belonging to historically marginalised populations. However, research on disparities in student mental health has almost exclusively focused on internalising problems (like symptoms of depression and anxiety), overlooking other ways in which individuals experience and express negative emotion. To address this limitation, the present study employed the Brief Problem Monitor to examine three types of mental health problemsinternalising, externalising, and attentional problemsacross six sociodemographic characteristics: gender (male vs. female), sexual orientation (heterosexual vs. non-heterosexual), ethnicity (Dutch without vs. with migration background), internationality (domestic vs. international), disability (no disabilities vs. disabilities), and parental education (continuing-vs. first-generation). These sociodemographic variables were included in regression models simultaneously, thereby controlling for the effects of the others. Across a sample of 2256 students, internalising problems were significantly higher in students who were female, non-heterosexual, international, and in those with disabilities. Higher externalising problems were found in female students, students with disabilities, those with a migration background, and first-generation students. Finally, attentional problems were higher in non-heterosexual students and students with disabilities. These findings support the premise that different groups of students experience different types of mental health concerns, emphasising the importance of measuring mental health multidimensionally. As an example, had the present study only examined internalising problems, we would not have found mental health disparities for students with a migration background and first-generation students, which has clear implications for outreach and resources offered to them.